Electrical Properties and Thermal Expansion Characteristics of (1–x)Ba0.948Ca0.05Er0.002Ti0.94Zr0.06O3–(x)Pr Lead‐Free Piezoelectric Ceramics Sintered at a Low‐Temperature. Issue 2 (19th November 2018) - Tian, Yongshang; Cao, Lijia; Li, Shuiyun; Fu, Shiying; Chen, Zhijia; Ji, Xiang; Jing, Qiangshan
Abstract : (1 −  x )Ba0.948 Ca0.05 Er0.002 Ti0.94 Zr0.06 O3 –( x )Pr ( x =  0–0.75 mol%) ceramics are sintered at 1240 °C by conventional solid‐state reaction method using the as‐synthesized nanoparticles, which are prepared by a modified Pechini method. The structural, morphological, electrical, and thermal expansion properties as a function of varying x are systematically investigated. All samples feature rhombohedral phase, and their lattice parameters are accurately calculated by Rietveld refinement software. Volume of oxygen vacancies initially decreases and then increases with increasing x, leading to diversified electrical properties. Deteriorated electrical properties of the ceramics with excessive x are attributed to the increment of defect complexes with a large volume of oxygen vacancies. The coefficient of thermal expansion values of the ceramics that is influenced by phase evolution and structure defects under different temperature ranges are studied. The respective optimal electrical properties, that is, d 33  = 186 pC N −1 and k p  = 27.2% are obtained at x  = 0.30 mol%. This research is believed to be insightful to practical application of the lead‐free multifunctional electron components. Abstract : In this work electrical and CTE properties of Er 3+ and Pr 3+ co‐doped BCEZT– x Pr ceramics, which are sintered with as‐synthesized nanoparticles by a modified Pechini method are evaluated. The diversified properties influenced by defect complexes and oxygen vacancies are emphatically studied, and their mechanism are explored. With excellent electrical and CTE properties, the ceramics possess potential application on multifunctional electron components.